Mali korak prema usustavljenju terminologije aspektologije na hrvatskome jeziku - Le Calvé Ivičević, Evaine; Pranjković, Iva (2019)
Brojni radovi posvećeni glagolskom vidu u različitim slavenskim, ali i u drugim jezicima u kojima ova kategorija nije morfološki obilježena, proizveli su obilje naziva te doveli do nejasnoća koje predstavljaju prepreke u razvoju aspektologije. U tradiciji radova koji opisuju glagolski vid i aspektna značenja u slavenskim jezicima pojedini se nazivi redovno pojavljuju, dok noviji nazivi nemaju nužno isto značenje pod perom svih autora koji ih koriste. No uz iznimku rijetkih članaka koji opisuju pojedine teme, nijedan autor nakon Đure Grubora nije pokušao razraditi cjelovito nazivlje koje bi udovoljilo potrebama za opisom aspektnih značenja u hrvatskome. Iz toga proizlazi potreba za preispitivanjem postojećih naziva i definicija pojmova koje označavaju kako bismo mogli ponuditi precizno osnovno nazivlje kao poticaj za nastavak istraživanja o aspektologiji. U prvom dijelu istraživanja ponudit ćemo pregled do sada korištenih naziva i pojmova u radovima posvećenim glagolskom vidu. U drugom dijelu predložit ćemo usustavljeno osnovno nazivlje i harmonizirane definicije u njemu označenih pojmova.
Numerous works devoted to the verbal aspect in the Slavic languages, as well as in other languages in which this category is not morphologically marked, have produced an abundance of terms, that is, terminological systems that vary, depending on a particular description. This abundance, encouraged by the progress of research, but also by the personal work of linguists dealing with different language families, has produced ambiguities that are obstacles to the development of aspectology and which are maintained in the very core of the Croatian language terminology (Novak Milić 2010: 131). In the tradition of works describing verbal and aspectual meanings in Slavic languages, certain terminological pairs commonly appear, describing ways of doing things such as “duration / punctuality”, “performing / accomplishment” etc. Newer terms, which are the fruits of personal work or which stem from the tradition of language schools, do not necessarily have the same meaning in the works of all the authors who use them. However, with the exception of the few articles describing some topics (Mršić 1999, Novak Milić 2010), no author after Đuro Grubor (1953a, 1953b) has attempted to elaborate a complete terminology that would meet the needs for describing aspects in Croatian. We assume that a systematized terminology would create a basis for deeper study of verbal aspect and, in general, aspectology, and would help to improve research on that subject in Croatian. This leads to the need for reviewing the existing terms and definitions of the concepts that they signify, so that we can offer a precise basic terminology as an incentive to continue the research on aspectology. In the first part of our work, we will provide an overview of the terms and concepts used so far in the works devoted to verbal aspect. In the second part, we propose a set of terms and harmonized definitions of designated concepts.
Bilješke uz tekst.
Bibliografija: str. 536-537.
Sažetak ; Abstract.
Keywords: Hrvatski jezik -- Glagolski vid -- Aspektologija -- Glagoli